An exploratory study into select technical key performance Indicators and estimated transfer fees in the 2nd division of the German Bundesliga - Horn, Carsten (Stellenbosch : Stellenbosch University, 2023)
Thesis (M Sport Sc)--Stellenbosch University, 2023.